2019
DOI: 10.1001/jamadermatol.2018.5215
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Treatment for Clinically Amyopathic Dermatomyositis at 4 Tertiary Care Centers

Abstract: Nonetheless, over half of this cohort found AA to be moderately or seriously financially burdensome, and the average out-of-pocket costs of $1354 is similar to the average out-ofpocket costs of $1418 for patients with psoriasis. 4 The reallife willingness to pay of this cohort reflects the consequences of AA on the everyday lives of patients. Although future work is required to confirm these results and determine their generalizability to the overall community of patients with AA, these findings suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…Pinard and researchers from four tertiary care centers evaluated treatments for 115 CADM patients. They found that antimalarials alone were effective in only 11.4% (10 out of 88) and immunosuppressants were given to 80% of whole patients ( 18 ). The most commonly used immunosuppressants were MTX ( n = 59, 51.3%) and MMF or mycophenolic acid ( n = 46, 40%).…”
Section: Resultsmentioning
confidence: 99%
“…Pinard and researchers from four tertiary care centers evaluated treatments for 115 CADM patients. They found that antimalarials alone were effective in only 11.4% (10 out of 88) and immunosuppressants were given to 80% of whole patients ( 18 ). The most commonly used immunosuppressants were MTX ( n = 59, 51.3%) and MMF or mycophenolic acid ( n = 46, 40%).…”
Section: Resultsmentioning
confidence: 99%
“…In a study of 41 patients with skin‐only dermatomyositis requiring systemic therapy, only 6 (14.6%) were sufficiently managed with hydroxychloroquine alone, with the remainder needing either a change to or addition of an alternative antimalarial, methotrexate, mycophenolate mofetil, azathioprine or intravenous gamma globulin. In another recent study of 115 patients with clinically amyopathic dermatomyositis, antimalarials were the most commonly used systemic agent; however, adequate control of the skin disease occurred in only 11.4% of these cases . Furthermore, 30.7% of the patients treated with hydroxychloroquine developed a cutaneous hypersensitivity reaction …”
Section: Clinical Applications In Dermatologymentioning
confidence: 99%
“…In another recent study of 115 patients with clinically amyopathic dermatomyositis, antimalarials were the most commonly used systemic agent; however, adequate control of the skin disease occurred in only 11.4% of these cases . Furthermore, 30.7% of the patients treated with hydroxychloroquine developed a cutaneous hypersensitivity reaction …”
Section: Clinical Applications In Dermatologymentioning
confidence: 99%
“…El 30,7 % de los pacientes tratados con hidroxicloroquina, desarrolló una reacción de hipersensibilidad cutánea. 40 Por otra parte, en el caso de la alopecia, un reporte en 2013 describió dos pacientes de alopecia totalis con excelente respuesta a la HCQ. Pero, una serie de casos posterior, de ocho pacientes con alopecia totalis y extensa alopecia areata, sugirió que la HCQ fue ineficaz.…”
Section: Efectos En Enfermedades Dermatológicasunclassified